Quantification of Carbon Cycling in a Large Aquifer Using Reactive Transport Modelling - Miotliński, Konrad; Peeters, Luk J. M. (Frontiers in Water, 2021)
Continental scale aquifers are capable of storing significant amounts of carbon as a result of immense water volumes, substantial concentrations of dissolved inorganic carbon (DIC) and its reactions with a matrix, thus contributing the global carbon storage and cycle. However, concentration of dissolved solutes may vary significantly over distances, which causes interpretative challenges and difficulties to in process quantification. This occurs in the Guarani Aquifer System in South America, which is a subject of extensive research due to a significant strategic role in water supply. Dissolved CO$_{2}$ is expected to dissociate and undergo reactions with aluminosilicate minerals, but it is unknown how much DIC may get immobilised in the aquifer. To quantify the processes, we performed reactive transport modelling which combines hydrological and geochemical information followed by global sensitivity analysis. We show that more than a half of the infiltrated CO$_{2}$ may be consistently precipitated as CaCO$_3$. The DIC concentrations across the aquifer depend primarily on the input carbon concentrations and the plagioclase hydrolysis rate, while other parameters including hydraulic conductivity, recharge rate and mineral stability are of the minor importance. We present how advanced modelling techniques may be used to interpret and quantify processes controlling water quality in continental scale groundwater systems.